Identification of Quantitative Trait Loci Associated With Partial Resistance to Fusarium Root Rot and Wilt Caused by Fusarium graminearum in Field Pea - Wu, Longfei; Fredua-Agyeman, Rudolph; Strelkov, Stephen E.; Chang, Kan-Fa; Hwang, Sheau-Fang (Frontiers in Plant Science, 2022)
Fusarium root rot, caused by a complex of Fusarium spp., is a major disease of field pea (Pisum sativum). The development of genetic resistance is the most promising approach to manage the disease, but no pea germplasm has been identified that is completely resistant to root rot. The aim of this study was to detect quantitative trait loci (QTL) conferring partial resistance to root rot and wilting caused by five fungal isolates representing Fusarium solani, F. avenaceum, F. acuminatum, F. proliferatum and F. graminearum. Evaluation of the root rot tolerant cultivar ‘00-2067’ and susceptible cultivar ‘Reward’ was carried out with the five species. There was a significant difference (p < 0.001) between the mean root rot values of the two cultivars inoculated with the F. avenaceum (F4A) and F. graminearum (FG2) isolates. Therefore, in the QTL study, the F8 recombinant inbred line (RIL) population derived from ‘Reward’ × ‘00-2067’ was inoculated in the greenhouse (4×) with only F4A and FG2. The parents and F8 population were genotyped using 13.2K single nucleotide polymorphisms (SNPs) and 222 simple sequence repeat (SSR) markers. A significant genotypic effect (P<0.05) and high heritability (79% to 92.1%) were observed for disease severity, vigor and plant height following inoculation with F4A and FG2. Significant correlation coefficients were detected among and within all traits. This suggested that a high proportion of the genetic variance was transmitted from the parents to the progeny. However, no significant QTL (LOD>3.0) were detected for the RILs inoculated with F4A. In the case of the RILs inoculated with FG2, 5 QTL for root rot severity and 3 QTL each for vigor and plant height were detected. The most stable QTL for plant height (Hgt-Ps3.1) was detected on Chrom5/LGIII. The two most stable QTL for partial resistance to FG2, Fg-Ps4.1 and Fg-Ps4.2, were located in a 15.1 cM and 11.2 cM genomic region, respectively, on Chrom4/LGIV. The most stable QTL for vigor (Vig-Ps4.1) was found in the same region. Twenty-five major and moderate effect digenic epistatic interactions were detected. The identified region on chrom4/LGIV could be important for resistance breeding and marker development.